Making sense of management : a critical introduction - Alvesson, Mats, 1956-; Willmott, Hugh; Sage eBooks (London : SAGE Publications, 2012)
'Making Sense of Management' provides a fresh perspective on management that explores how the disruptive and constructive potential of critical theory can be realised in organizations.
Previous edition issued in print: 1996.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 16, 2014).
Keywords: Management; Critical theory; Electronic books